WŁAŚCIWOŚCI ZACHOWANIA SIĘ WIELKOŚCI EKONOMICZNYCH W CZASIE CYKLU KONIUNKTURALNEGO W POLSCE - Gaweł, Aleksandra (Wydział Prawa i Administracji UAM, 1999)
The Author discusses peculiarities of foundamental parameters of the economic life under business cycle in Poland during the recent period of system transformation. In this respect an analysis of interdependences in fluctuations of the National Gross Product - seen as a referential sequence - and of such parameters as factory prices and consumer’s prices, profits of the enterprises, investments and, finally, money supply. Thanks to this proceeding a pro-cyclic or anti-cyclic character of correlations between all of these data could be determinated. Additionally, mutual relations between production and consumption, production and investments, employment and salaries, savings and investments, as well as between budget outcome and foreign trade balance - have been presented in the article. The whole of this analysis was to indicate whether the regularities taking place within the business cycle in Poland do really correspond with phenomenons proper to higher developed market economies. It came out however that there are only a few of common features. A business cycle under transformation period has rather its own specificity which is well apart.
PECULIARITIES OF THE COURSE OF MAIN ECONOMIC PARAMETERS UNDER BUSINESS CYCLE IN POLAND